2005
DOI: 10.1177/1469787405054238
|View full text |Cite
|
Sign up to set email alerts
|

Analysing student perceptions of transferable skills via undergraduate degree programmes

Abstract: M I K E D O H E RT Y University of Luton, UKA B S T R AC T Despite the assumption that 'transferable' skills are part and parcel of a graduate's portfolio, there is a lack of information about the extent to which such skills may be perceived by students to be valuable. Although the skills agenda has been at the forefront of Higher Education (HE) provision for some time, contemporary studies focus upon measurement issues and neglect the process aspects of skills learning and development. There is also a lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 6 publications
0
36
0
5
Order By: Relevance
“…skills which are applicable outside of university, is now considered an integral aspect of the doctoral process (Saunders, 2010). However, despite attention drawn to the onus for undergraduate students to gain and demonstrate an array of industry relevant skills upon graduation (Burke, Jones, & Doherty, 2005), less attention has focused on the opportunities for doctoral students to do so. It has also been suggested that doctoral education is to a certain extent, incompatible with the accumulation of such generic skills (Gilbert, Balatti, Turner, & Whitehouse, 2004), those necessary to the pursuit of careers beyond academia (which the majority of doctoral students do upon completion of their studies).…”
Section: Transferable and Generic Skillsmentioning
confidence: 99%
“…skills which are applicable outside of university, is now considered an integral aspect of the doctoral process (Saunders, 2010). However, despite attention drawn to the onus for undergraduate students to gain and demonstrate an array of industry relevant skills upon graduation (Burke, Jones, & Doherty, 2005), less attention has focused on the opportunities for doctoral students to do so. It has also been suggested that doctoral education is to a certain extent, incompatible with the accumulation of such generic skills (Gilbert, Balatti, Turner, & Whitehouse, 2004), those necessary to the pursuit of careers beyond academia (which the majority of doctoral students do upon completion of their studies).…”
Section: Transferable and Generic Skillsmentioning
confidence: 99%
“…Research to understand students' perceptions of the varied differing learning environments they are exposed to (Burke, Jones & Doherty, 2005) reflect the vagaries of flexible pedagogy highlighted by Barnett (2014). Yet the learning environment is key to developing the knowledge and skills required by today's graduate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Il nécessite le transfert des théories à la pratique (Burke, Jones et Doherty, 2005 ;Fritz, 2006 ;Val Klenowski et Carnell, 2006), autrement dit la prise de conscience de l'impact des apprentissages sur la pratique (Allen, 2004 …”
Section: Contexte Théoriqueunclassified